Case report: Emergency management of spontaneous rupture of the inflammatory myofibroblastic tumor of the urinary bladder - Sun, Zhenfu; Qi, Lei; Guo, Zhifan; Yuan, Wei; Du, Yuancheng; Gao, Haitao; Hong, Xuekai; Zang, Yunjiang (Frontiers in Oncology, 2022)
Acute abdomen caused by spontaneous rupture of the inflammatory myofibroblastic tumor of the urinary bladder (IMTUB) is a rare clinical emergency of the urinary system.It is difficult to distinguish it from spontaneous rupture of bladder caused by other causes before surgery. An emergency case of spontaneous rupture of IMTUB was reported. A 57-year-old middle-aged woman was admitted to the hospital because of "acute lower abdominal pain for 5 hours". No history of smoking and gross hematuria. The physical examination revealed visible abdominal tenderness as well as signs of shock. A pelvic CT scan shows a space-occupying lesion above the bladder with massive accumulation of blood. When the nature of the tumor could not be determined, emergency laparotomy and partial cystectomy were performed, and postoperative pathology confirmed cystitis myofibroblastic tumor. No local recurrence or distant metastasis of the tumor was observed during the regular follow-up period of 6 months. IMTUB should focus on prevention and treatment, with a combination of preoperative examination and postoperative pathology, and finally implement highly individualized treatment.